Models of joint defaults in credit risk management: an assessment - Erlenmaier, Ulrich (SSRN, 2001)
In this paper we review the models of joint defaults of the current major industry-sponsored credit risk frameworks. Recognizing the need for further improvements of these models, we address the following issues. First, we identify the most important modeling drawbacks that could be fixed on a short-term basis. Second, we analyze which of the proposed models is the conceptually most promising basis for next-generation models. Concluding that the KMV methodology is the most suitable to go forward, we set out a research agenda aiming at further improvements and at extending the KMV model to non-quoted firms